EXTRACTION OF FLAVONOIDS FROM GREEN TEA AND ITS IN VITRO EFFICACY AGAINST SOME SELECTED MICROBES - ARNAB DEB,; RAJESH P JAYASWAL,; PRANAY PUNJ PANKAJ, (International Journal of Pharma and Bio Sciences, 2016)
Green tea (Camellia sinensis) consists of various bioactive components which is useful in new kind of formulation to treat the human diseases. Micro-organisms became resistant to varieties of antibiotics so natural herbal remedy is needed to combat the microbial infections. In the present study, polyphenols such as MQK (myricetin, quercetin, kaempferol) and EGCG (epigallocatechingallate) and C (catechin) were extracted from green tea (Camellia sinensis) leaves and tested against test bacteria and fungi. Different concentrations of these polyphenols were examined for antibacterial activities by disc diffusion method. Antimicrobial assay showed significant zone of inhibition against S. aureus (Gram positive bacteria), P. vulgaris (Gram negative bacteria), Cryptococcus sp.(fungus) and Penicilium sp. (fungus). Catechin showed broad spectrum antibacterial and antifungal activities. Minimum inhibitory concentration (MIC) of catechin was 3.12 mgdl-1 against S. aureus, P. vulgaris and Cryptococcus sp. whereas at 6.25 mgdl-1 inhibited Penicilium sp. MQK and EGCG were especially effective against Cryptococcus sp and Penicilium sp.which gave MIC value of 6.25 mgdl-1. EGCG at same concentration was also effective against P. vulgaris. This study suggests the therapeutic use of green tea against bacterial as well as fungal infections.